Pengaruh Promosi terhadap Keputusan Pembelian Air Minum dalam Kemasan: Studi Kasus CV. Zam Zami Alget Panyabungan Timur Kabupaten Mandailing Natal - Alliriansah Alliriansah; Vebri Sugiharto; Muhlisah Lubis (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research aims to determine the effect of promotions on CV drinking water purchasing decisions. Zam Zami Alget. Promotions have a significant impact on CV drinking water purchasing decisions. Zam-Zami- Alget, through effective promotional strategies, such as advertising, discounts, or loyalty programs, consumers become more aware of products and tend to choose them because of the perceived added value offered. This research was carried out at CV. Zam Zami Alget, East Panyabungan District, Mandailing Natal Regency. This research method used is quantitative by describing the data using numbers. The sample of this research was 30 people using a quantitative approach. The results of simple linear regression analysis using SPSS version 25 produced the equation Y=17.394+ 0.524. Data analysis using the t test obtained a calculated t result of 3,790 and a t table at the 5% significance level of 1.701, so t calculated > t table and the significance value was 0.001 < 0.05. This shows that there is a promotional influence on the decision to purchase CV drinking water. Zam Zami Alget Alget, East Panyabungan District, Mandailing Natal Regency.